2023
DOI: 10.3390/genes14071426
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Antibiotic Synergy Combinations for Eliminating Colistin Heteroresistant Klebsiella pneumoniae

Sahaya Glingston Rajakani,
Basil Britto Xavier,
Adwoa Sey
et al.

Abstract: Colistin heteroresistance has been identified in several bacterial species, including Escherichia coli and Klebsiella pneumoniae, and may underlie antibiotic therapy failures since it most often goes undetected by conventional antimicrobial susceptibility tests. This study utilizes population analysis profiling (PAP) and time–kill assay for the detection of heteroresistance in K. pneumoniae and for evaluating the association between in vitro regrowth and heteroresistance. The mechanisms of colistin resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Isolates AN1505CP2 and IT0244CP were previously already determined to be CHR [ 16 ]. In this study, these findings were confirmed with both isolates fulfilling C1, and colonies from each plate were sequenced (data not published).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolates AN1505CP2 and IT0244CP were previously already determined to be CHR [ 16 ]. In this study, these findings were confirmed with both isolates fulfilling C1, and colonies from each plate were sequenced (data not published).…”
Section: Resultsmentioning
confidence: 99%
“…An isolate was classified as susceptible (MIC ≤ 2 mg/L) or resistant (MIC > 2 mg/L) based on the epidemiological cut-off (ECOFF) values provided by EUCAST [ 15 ]. Two CS strains, Escherichia coli ATCC 25922 (MIC: 0.25–2 mg/L) and P. aeruginosa ATCC 27853 (MIC: 0.5–4 mg/L), and two CR strains, K. pneumoniae 08400 (MIC: 64 mg/L) and E. coli NCTC 13846 mcr-1 positive (MIC: 4 mg/L), were used as controls [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation